A pharmacological master key mechanism that unlocks the selectivity filter gate in K+ channels - Schewe, M; Sun, H; Mert, Ü; Mackenzie, A; Pike, A; Schulz, F; Constantin, C; Vowinkel, K; Conrad, L; Kiper, A; Gonzalez, W; Musinszki, M; et al. (American Association for the Advancement of Science, 2019)
Potassium (K + ) channels have been evolutionarily tuned for activation by diverse biological stimuli, and pharmacological activation is thought to target these specific gating mechanisms. Here we report a class of negatively charged activators (NCAs) that bypass the specific mechanisms but act as master keys to open K + channels gated at their selectivity filter (SF), including many two-pore domain K + (K 2P ) channels, voltage-gated hERG (human ether-à-go-go–related gene) channels and calcium (Ca 2+ )–activated big-conductance potassium (BK)–type channels. Functional analysis, x-ray crystallography, and molecular dynamics simulations revealed that the NCAs bind to similar sites below the SF, increase pore and SF K + occupancy, and open the filter gate. These results uncover an unrecognized polypharmacology among K + channel activators and highlight a filter gating machinery that is conserved across different families of K + channels with implications for rational drug design.